(untitled) (Research, Society and Development, 2023)
The search for alternative treatments and different clinical uses of medicinal cannabis has shown significant growth in recent years. In this context, this study aims to evaluate the use of medicinal cannabis as a treatment for opioid use disorders. Through a systematic analysis, using the PubMed and Medline databases, a search was carried out, giving preference to clinical trials, meta-analyses and bibliographic reviews from the last 10 years, in animals and humans using the terms “cannabis”, “opioids”, “addiction” and “treatment”. Articles with the terms “smoker”, “smoking” and “pregnant” in the title or abstract were excluded, and ongoing studies were also excluded. A reduction in withdrawal symptoms was observed, with a prolonged effect and a good safety profile. Studies show positive preliminary results, however, they have small samples, without standardization of synthetic cannabinoids and their respective dosages. Therefore, studies with standardization of parameters and a larger sample number are necessary for assertive conclusions.